Associations of Estrogen Receptor Alpha Gene Polymorphisms with Type 2 Diabetes Mellitus and Metabolic Syndrome: A Systematic Review and Meta-Analysis - Yang, Jiajia; Han, Renfang; Chen, Mengya; Yuan, Yaping; Hu, Xingxing; Ma, Yubo; Wu, Meng; Zhang, Xu; Wang, Mengmeng; Jiang, Shanqun; Pan, Faming (Hormone and Metabolic Research, 2018)
The associations between PvuII (T>C) and XbaI (A>G) polymorphisms of estrogen receptor alpha (ESR1) gene with type 2 diabetes mellitus (T2DM) or metabolic syndrome (MetS) are reported in many studies, but the results are inconsistent. This present work aims to assess the associations by performing a comprehensive meta-analysis. Relevant studies were searched through several databases. The pooled odd ratios (ORs) with 95% confidence intervals (CIs) were calculated to evaluate the associations of PvuII and XbaI polymorphisms with the risk of T2DM and MetS by using the STATA 14.0 software. Eight studies for T2DM and three articles about MetS were included in this meta-analysis. The overall results indicated that PvuII, rather than XbaI polymorphism, was associated with T2DM (regressive model: OR=0.673, 95% CI=0.550 to 0.823, praw<0.001, pFDR<0.003). The subgroup analysis based on race revealed an association of PvuII polymorphism with the decreased T2DM risk in Chinese population and a relationship between XbaI polymorphism and the reduced T2DM susceptibility in Caucasians. The difference of country may be one source of the heterogeneity for PvuII polymorphism and T2DM. However, neither PvuII nor XbaI polymorphism was related to the risk of MetS. The C allele of PvuII polymorphism presents a protective role in T2DM risk, especially in Chinese people. The G allele of XbaI polymorphism is related to a reduced risk for T2DM in Caucasian population. Nevertheless, neither of PvuII nor XbaI polymorphism is associated with MetS risk.
Keywords: Estrogen receptor alpha; type 2 diabetes mellitus; metabolic syndrome; meta-analysis